PENGARUH METODE STORYTELLING BERBANTUAN MEDIA FLIPBOOK TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SEKOLAH DASAR - Sapitri, Intan; Nisa, Uswatun; Koswara Adiredja, Rajji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are crucial for supporting elementary school students' communication, yet in practice, their proficiency remains low. This is characterized by limitations in sentence structure, lack of confidence, and difficulty conveying ideas coherently. One approach to addressing these issues is the implementation of storytelling methods using flipbooks, which can create interactive and engaging learning. This research employed a quantitative approach with an experimental design and a one-group pretest-posttest design. The subjects were 39 fifth-grade students at SDN 2 Hegarsari. Data collection used a speaking skills performance test covering both linguistic and non-linguistic aspects. Data analysis was conducted using descriptive and inferential statistics using the Shapiro-Wilk normality test and a paired sample t-test. The results showed an increase in the average score from 43.46 in the pretest to 67,82 in the posttest, with a significance level of 0.000 <0.05. This improvement occurred because the storytelling method provided students with the opportunity to practice composing and conveying stories orally, while the flipbook media helped students understand the storyline through engaging visualizations, making it easier to remember and retell. Consequently, there was improvement in linguistic aspects, such as vocabulary, sentence structure, intonation, and pronunciation as well as non-linguistic aspects, such as confidence, fluency, expression, volume, and topic mastery. Thus, the integration of the storytelling method and flipbook media has proven effective in improving elementary school students' speaking skills and can be used as an innovative, interactive, and contextual learning alternative